E-Id Card Services Under The Kelingan Adminduk Program of The Cirebon Regency Civil Registration and Population Administration Office - Adinda Maharani Budiana Raharjo; Rd. Mahendra Haryo Bharoto (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Service quality in population administration services is an important factor in increasing public satisfaction. This study aims to analyze the quality of e-KTP (Elektronik Kartu Tanda Penduduk) services in the Kelingan Adminduk program of the Cirebon Regency Population and Civil Registration Agency (Dinas Kependudukan dan Pencatatan Sipil/DISDUKCAPIL). The research method used is a descriptive qualitative method. Data collection was carried out through observation, interviews, and documentation. The collected data were analyzed using thematic analysis, which involves the processes of data coding, identifying patterns or themes, and interpreting the meaning of each thematic category. The results of this study lead to the conclusion that the e-KTP service in the Kelingan Adminduk program of the Cirebon Regency Population and Civil Registration Agency (DISDUKCAPIL) has been running well but cannot yet be considered of high quality. This can be seen from the existing services in the Kelingan Adminduk program, which are measured using five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. However, there are still several challenges in its implementation, such as uncertain e-KTP printing times and inadequate human resources. It can be concluded that, in order to improve service quality, sufficient human resources and stronger planning are needed so that public satisfaction can be increased.